The Class I PI3K inhibitor S14161 induces autophagy in malignant blood cells by modulating the Beclin 1/Vps34 complex - Siyu Wang; Jie Li; Yanyun Du; Yujia Xu; Yali Wang; Zubin Zhang; Zhuan Xu; Yuanying Zeng; Xinliang Mao; Biyin Cao (Elsevier, 2017)
S14161 is a pan-Class I PI3K inhibitor that induces blood cancer cell death, but its mechanism is largely unknown. In the present study, we evaluated the role of S14161 in autophagy, an emerging event in cell destination. Multiple myeloma cell lines RPMI-8226, OPM2, KMS11 and leukemia cell line K562 were treated with S14161. The results showed that S14161 induced autophagy as demonstrated by increased LC3-II and decreased p62, which were prevented by autophagy inhibitors including 3-methyladenine and bafilomycin A1. Mechanistic studies showed that S14161 had no effects on Vps34 expression, but increased Beclin 1 and decreased Bcl-2, two major regulators of autophagy. Furthermore, S14161 dissociated the Beclin 1/Bcl-2 complex and enhanced the formation of Beclin 1/Vps34 complex. Moreover, S14161 inhibited the mTORC1 signaling transduction. S14161 downregulated activation of mTOR and its two critical targets 4E-BP1 and p70S6K, suggesting S14161 inhibited protein synthesis. Taken together, these results demonstrated that Class I PI3K regulates autophagy by modulating protein synthesis and the Beclin 1 signaling pathway. This finding helps understanding the roles of PI3K in autophagy and cancer treatment.